2001
DOI: 10.1164/ajrccm.164.3.2007168
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Inhibits Epithelial Sodium Channels in Patients with Cystic Fibrosis

Abstract: The aim of this study was to determine the effects of a single exercise bout on luminal Cl(-) and Na(+) conductance in the respiratory epithelium of patients with cystic fibrosis (CF). In nine patients with CF and nine healthy control subjects, the transepithelial electrical potential difference (PD) of the nasal respiratory epithelium was recorded, first at rest and then during moderate-intensity exercise. Under both conditions, PD was first measured while superfusing the epithelium with isotonic saline. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 18 publications
5
57
2
2
Order By: Relevance
“…This results in cell injury and release of mediators, such as histamine, prostaglandins and leukotrienes, from mast cells, causing bronchial smooth muscle contraction [8]. In healthy individuals, sympathoadrenergic activation during exercise stimulates fluid secretion by activating Cl -channels such as CFTR and by decreasing fluid reabsorption from the airways [9]. However, secretion may not always match the loss of water.…”
mentioning
confidence: 99%
“…This results in cell injury and release of mediators, such as histamine, prostaglandins and leukotrienes, from mast cells, causing bronchial smooth muscle contraction [8]. In healthy individuals, sympathoadrenergic activation during exercise stimulates fluid secretion by activating Cl -channels such as CFTR and by decreasing fluid reabsorption from the airways [9]. However, secretion may not always match the loss of water.…”
mentioning
confidence: 99%
“…Hommerding et al [30] found no significant improvement in QoL domains after an education intervention of PA for children and adolescents with CF. Another study reported that QoL was associated with physical fitness and to a lesser extent with reported PA [28]. We can speculate that participation in PA could not directly increase QOL perception, but might improve subjects' self-esteem and consequently their adherence to exercise programs.…”
Section: Discussionmentioning
confidence: 84%
“…Hebestreit et al [28] showed that in CF subjects V'O 2 peak correlate positively with QOL. Cox et al [4] reported higher scores in QoL by adult subjects with CF who performed ≥ 30 minutes of moderate-vigorous PA daily compared to those who performed <30 minutes daily.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations